The urban commuter cyclist trousers design with a sustainable design approach - Naufal Arya Putra Nurjaman; Hanif Azhar; Terbit Setya Pambudi; Alvian Fajar Setiawan; Tasya Natalia Wijaya; Antonio Junico Da Cruz Soares; Devi Eka Agustin (Institut Seni Indonesia Yogyakarta, 2023)
After the prolonged COVID-19 pandemic, we have entered the New Normal phase with all adjustments and adaptations to new post-pandemic habits. Throughout 2020 and 2021 cycling has become a trend for a healthy lifestyle that people are interested in. With the rise of people cycling, sales of bicycles and their supporting equipment such as apparel have also increased. Seeing the trend of cycling and commuter bike riders who use bicycles as the main mode of transportation for daily mobilization, this becomes a potential for designing cargo pants for commuter bike riders with a sustainable design approach. Cargo pants are versatile pants that prioritize utility with various compartments that can fit various user items. Exploration of the features and systems in the design product is expected to meet the needs of commuter bike users and provide alternative products to users.